2021
DOI: 10.1073/pnas.2020524118
|View full text |Cite
|
Sign up to set email alerts
|

Intracounty modeling of COVID-19 infection with human mobility: Assessing spatial heterogeneity with business traffic, age, and race

Abstract: The COVID-19 pandemic is a global threat presenting health, economic, and social challenges that continue to escalate. Metapopulation epidemic modeling studies in the susceptible–exposed–infectious–removed (SEIR) style have played important roles in informing public health policy making to mitigate the spread of COVID-19. These models typically rely on a key assumption on the homogeneity of the population. This assumption certainly cannot be expected to hold true in real situations; various geographic, socioec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 68 publications
(57 reference statements)
1
69
0
Order By: Relevance
“…Previous studies concluded that people of color had experienced heightened COVID-19 infections and more deaths on average than white individuals (APM Research Lab, 2021 ). Besides, spatial heterogeneities were significant in COVID-19 infections (Hou et al, 2021 ; Thomas et al, 2020 ). The neighborhoods where COVID-19 gathered were likely where the vulnerable population lived (Hong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies concluded that people of color had experienced heightened COVID-19 infections and more deaths on average than white individuals (APM Research Lab, 2021 ). Besides, spatial heterogeneities were significant in COVID-19 infections (Hou et al, 2021 ; Thomas et al, 2020 ). The neighborhoods where COVID-19 gathered were likely where the vulnerable population lived (Hong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as China is the largest developing country in the world, studies on the transmission, modeling, and understanding of COVID-19 in China should explore the urban environmental factors that influence the distribution and transmission of COVID-19, taking into account urban public health resources. Such research is likely to be of great regional value (Hou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of the COVID-19 pandemic, the 2020 US presidential election was destined to be unusual. The spread of the coronavirus disease in the USA embodies significant spatial heterogeneity due to varying population density and structure, social economics, political attitude, and COVID-19 control policies in different places (Hou et al 2021 ; Sun et al 2020 ; Desmet and Wacziarg 2020 ), and partisan divides on state and local COVID-19 response policies have become even starker (Iyengar and Westwood 2015 ; Sides et al 2020 ). Research suggests that the COVID-19 pandemic may have caused potential political shifts (Johnson et al 2020 ), and the COVID-19 related health disparity issues have influenced the 2020 US election and presidential campaigns in multiple aspects (Norris and Gonzalez 2020 ).…”
Section: Introductionmentioning
confidence: 99%